Thailand Economic Monitor, January 2021 : Restoring Incomes, Recovering Jobs - World Bank Group (World Bank, Bangkok, 2021)
The Thailand Economic Monitor (TEM) reports on key developments in Thailand’s economy over the past six months, situates these changes in the context of global trends and Thailand’s longer-term economic trajectory, and updates Thailand’s economic and social welfare outlook. Each edition of the TEM also provides an in-depth examination of selected economic and policy issues and an analysis of Thailand’s medium-term development challenges. The TEM is intended for a wide audience, including policymakers, business leaders, financial-market participants, and the community of analysts and professionals engaged in Thailand’s evolving economy.